Educação permanente em saúde para equipes de saúde da família: percepções, práticas e desafios - Marques, Emilly Souza (2016)
The study aimed to analyze the perceptions, practices and challenges related to Permanent Education in Health from interprofessional teams of Family Health Strategy in Maceió, Alagoas, Brazil. Therefore, a qualitative research was developed with the follow data collect techniques: tool for characterization, self-assessment in relation of Permanent Education and teams qualification; and Focus Group. In Maceió city, 32 health professionals from 04 Health Family teams took part of the research. After record and transcript the focus groups, the empirical material was organized, categorized and analyzed considering the Content Analysis, in thematic modality. The dialogic education theory, from Paulo Freire, was adopted for critical comprehensive of work process configuration as a fruitiful field for learning/emancipation or alienation/subordination, in regard of the relation between men and their acting in face to reality, and their potentiality to change the praxis in health. The results demonstrated the follow themes: I) Perceptions of Permanent Education in Health – the professional thinking: in which the teams showed contradictions in Permanent Education definition, presenting as a synonym of Continuing Education or transmission of knowledge to population or pointing the Permanent Education in a action-reflection-action movement. II) Practices of Permanent Education in Health – the professional acting: in which the teams linked the practices of Permanent Education developed in the health services with team´s meetings, educative groups in health and participation in scientific events. And III) Challenges and possibilities of Permanent Education in Health – the professional looking: in which the teams pointed as mainly challenges: to face the hegemony of biomedical model, the technical and hierarchical division of work; overwork and poor working conditions; and difficulties related to the articulation and resolution capacity of the services that compose the health care network. The professionals emphasized the strengthening of interprofessional team work, the self-care and the Matricial Support in Primary Health Care as possibilities to develop the Permanent Education. The study conclusion point to a professional context immerse in potentialities and advances, already being possible to identify transition points conducing to a new model to make health, in a perspective of dialogue and collective construction. Some examples of potentialities identified were: the recognition of the need for education as constant practice interlinked to daily work, the articulation with universities and Centers of Health Family Support, and the interaction, friendship and bond developed among the professionals of health teams.